EFEKTIVITAS PELAKSANAAN PROGRAM TANGGUNG JAWAB SOSIAL PERUSAHAAN PT. PERTAMINA (PERSERO) UNIT PEMASARAN I MEDAN DI LINGKUNGAN XII KELURAHAN SILALAS KECAMATAN MEDAN BARAT - DHAHRAN MANOGI M. (Welfare StatE, 2013)
PT. Pertamina (Persero) Unit Pemasaran I Medan is a well known State Owned Corporation with operation for marketing and distributing the product of downstream manufacturing of oil, gas and natural petroleum. This state corporation is also charging and responsible for supplying the oil requirement under region of Aceh, Sumatera Utara and Riau provinces. As one of biggest corporation scaled national and international, PT. (Persero) Unit Pemasaran I Medan has a burden with responsibility to conduct a governmental program in social responsibility, there is established a special division is under one special unit well known as Corporate Social Responsibility and also known local named Program Kemitraan Bina Lingkungan (PKBL) under both the Financial Manager and Public Relation Manager. The corporation is obliged to support the social surrounding and public around. The objective of this study is to know how effective the implementation of corporation program under social responsibility with PT. Pertamina (Persero) Unit Pemasaran I Medan, that has been provided on Lingkungan XII Kelurahan Silalas Kecamatan Medan Barat local area. Based on the result of analysis with the data obtained at least in six indicators the effectiveness of corporate social responsibility, such as: the understanding of program, achieving target accorded, noted timely, achieving the target, obtained the goal and the real change in reality. It has been taken conclusion that the implementation of program in corporate social responsibility has run effectively with total percentage of 55.72%. Following the unit affiliated and already united a special part under the program of corporation social responsibility, that mostly respondents further got job and have additional income, the length service to work become rising and also shift their paradigm in thinking around social, it means enriching also to those social surrounding in welfare with family as well as. The data, has been also supported by the effectiveness of implementing the program of corporate social responsibility, there has been done under likert scale in higher classified with average score obtained of 3.28. Keywords : effectiveness, corporate social responsibility, government program.